2019
DOI: 10.21873/anticanres.13357
|View full text |Cite
|
Sign up to set email alerts
|

The Epigenetic Modifier 5-Aza-2-deoxycytidine Triggers the Expression of CD146 Gene in Prostate Cancer Cells

Abstract: Background/Aim: During cancer progression cells undergo epithelial-to-mesenchymal transition (EMT).Although EMT is a complex process, recently, it has been reported that CD146 overexpression in prostate cancer cells is sufficient to induce mesenchymal phenotype. The following study aimed to investigate whether the expression of CD146 is altered by an epigenetic modifier in prostate cancer cells, in vitro. Materials and Methods: Three human prostate cancer cell lines were treated with 5-aza-2-deoxycytidine; the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…However, de novo hypermethylation of canonical CpG islands has been observed in cancer cells in association with inactivation of gene expression (Jones & Baylin, 2007). Although we observed the CpG island methylation of the CD146 promoter in 2 out of 3 analysed breast cancer cell lines, it does not have to be the only and unique methylated region which controls CD146 expression, since in the T47D breast cancer cell line and three prostate cancer cell lines published previously (Dudzik et al, 2019), the CD146 expression was induced by demethylating treatment, while the analysed CpG island was methylation free. Importantly, recent studies revealed that methylation in the upstream and downstream CpG island shores may inhibit gene transcription in cancer cells, whereas the CpG island itself can remain methylation free (Rao et al, 2013;Irizarry et al, 2009).…”
Section: Discussionmentioning
confidence: 38%
See 4 more Smart Citations
“…However, de novo hypermethylation of canonical CpG islands has been observed in cancer cells in association with inactivation of gene expression (Jones & Baylin, 2007). Although we observed the CpG island methylation of the CD146 promoter in 2 out of 3 analysed breast cancer cell lines, it does not have to be the only and unique methylated region which controls CD146 expression, since in the T47D breast cancer cell line and three prostate cancer cell lines published previously (Dudzik et al, 2019), the CD146 expression was induced by demethylating treatment, while the analysed CpG island was methylation free. Importantly, recent studies revealed that methylation in the upstream and downstream CpG island shores may inhibit gene transcription in cancer cells, whereas the CpG island itself can remain methylation free (Rao et al, 2013;Irizarry et al, 2009).…”
Section: Discussionmentioning
confidence: 38%
“…To our knowledge, this is the first study showing methylation of the CD146 promoter region in breast cancer cells, and concomitantly suggesting that an epigenetic mechanism may be important in expression control of this relevant metastasis related-oncogene. In our previous paper, using prostate cancer cell lines, we have shown that the CD146 gene is induced by a demethylating compound, 5 aza-2-deoxycytidine, however, analysis of the CpG island region in those cells did not confirm presence of promoter methylation (Dudzik et al, 2019). Of note, the link between epigenetics and expression of the CD146 gene was reported previously in prostate cancer patients but the authors of that study incorrectly localized the CpG island in the CD146 gene promoter (Liu et al, 2008), and in consequence misinterpreted the results suggesting, contrary to the dogma, that presence of the CpG island methylation correlates with increase in the CD146 gene expression in prostate cancer cells (Liu et al, 2008).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations